The New Testament : its history and theology - Price, James L. (James Ligon); Price, James L. (James Ligon), 1915- (New York : Macmillan, 1987)
Rev. ed. of: Interpreting the New Testament. 2nd ed. 1971.
Bibliography: p. 460-482 Includes index
Keywords: Bible. N.T. -- Introductions